HUBUNGAN KEKUATAN OTOT LENGAN DAN KESEIMBANGANSTATISDENGAN JAUHNYA LEMPARAN TURBO - Adi Suriatno; Rusdiana Yusuf (Lembaga Penelitian dan Pendidikan Mandala, 2019)
This study aims to determine whether there is a Relationship of Muscle Arm Strength And Stainless Equilibrium With Turbo Shot Deep In